Development of Energy Harvesting Method Using Shock Absorber - Fauzi Omar, Mohamad; Che Mat Haris, Harizan; Nawawi Seroji, Mohammad; Noraishah Wan Abdul Munim, Wan (International Journal of Engineering and Technology, 2018)
An alternative of power source need to be discovered in order to reduce the dependency on general power source such as fuel by making use of the waste energy. Power bump technology is one of the alternative power sources by using pressure. The conversion of the pressure from the external force is exerted by using process of transfer one form of energy to another. The term of free of charge energy coming from the force where it is converted to the potential energy force and that energy is being used. The generated free energy can increase efficiency and the output of productivity. This paper provides a full picture of the force utilization created from the effect of shock absorber of motorcycle bump an alternative power source. This paper also analyzes the pressure and force principle of Energy Harvesting in contributing to a new energy recovery technology. A model of shock absorber is utilized in order to harness energy from its upward and downward movement which create force that rotates the generator connected to the absorber. The application of the generator motor into the shock absorber will not affect the suspension system. It transforms the applied force into electrical energy. Mechanical parts are used for the harnessing process and conversion process. The harvested electrical energy can be either used directly to charge the battery or directly light up the bulb of the motorcycle.Â